Polymerization Rate Modulated by Tetraarylborate Anion Structure: Direct Correlation of Hammett Substituent Constant with Polymerization Kinetics of 2-Hydroxyethyl Methacrylate - Santos, Willy G. [UNESP]; Mattiucci, Fernando; Ribeiro, Sidney J. L. [UNESP] (American Chemical Society (ACS), 2018)
A series of para-substituted tetraarylborates were investigated as aryl radical generator for photopolymerization reactions, using 2-hydroxyethyl methacrylate as monomer. The first steps of the photopolymerization process involve the use of tetraarylborate as monocomponent photoinitiator or combination of two-component systems (riboflavin and tetraarylborate anion) to generate the aryl radical species, which is used to initiate the radicalar polymerization of vinyl monomers. Both photoinitiator systems herein investigated are very attractive for vinyl polymerization upon light irradiation. The polymerization and photochemical results indicate that the changes on the para-substituted ligand may be used to improve the formation of aryl radical species and the rate constant of electron transfer into two-component systems. In consequence of this reaction, the kinetics of radical polymerization is also modulated by electron donor/acceptor features of para-substituent ligands.